Hydrogeochemistry in groundwaters of Barreiro, Araxá City, Minas Gerais State, Brazil - Mancini, Luis Henrique [UNESP]; Bonotto, Daniel Marcos [UNESP] (My University, 2014)
Alkaline rocks in southern Brazil vary considerably in age and composition, and have been assembled into distinct geographic provinces that are particularly important due to the presence of economical deposits like the renowned carbonatite intrusion of Araxá. The Araxá complex has been reported in literature as Barreiro and is situated about 6 km from Araxá city, Minas Gerais State. It consists of a circular intrusion, 4.5 km in diameter, with the central part mainly formed by a carbonatite predominantly beforsitic in composition. Additional lithologies include mica-rich rocks, phoscorites and lamprophyres, where all these rock types affect the chemical composition of groundwaters occurring at the Barreiro area. This chapter reports the results of a hydrochemical survey held at the Barreiro area, where several monitoring wells have been sampled in order to provide information on the groundwater quality. Two fieldwork campaigns for groundwater sampling were realized in this study, they comprise the wet and dry seasons. The samples were analyzed in situ for physical parameters and stored in 1-L polyethylene bottles for chemical analyses. The water table depth, temperature and conductivity readings were performed in situ on using YSI probe, whereas the pH and redox potential (Eh) data were acquired by a Digimed portable meter. The water samples for chemical analysis were transported up to LABIDROIsotopes and Hydrochemistry Laboratory, Rio Claro city, São Paulo State, Brazil. They were filtered in 0.45 μm Millipore membrane for retaining the suspended solids before characterizing the major compounds in the liquid phase. The Hach DR 2000 spectrophotometer was utilized for yielding data for silica, tannin/lignin, alkalinity (as bicarbonate), magnesium, calcium, barium, nitrate, sulfate and phosphate. The sodium, chloride and fluoride measurements were done by potentiometry through Orion combined electrodes. The insertion of the pH and Eh data in an EhpH diagram indicated that the obtained data are inserted within a transition zone, tending to exhibit a reducing character, where a highly reducing value was found in the sampling held in the dry season. It was found inverse Eh-pH relationships in both fieldwork campaigns. Bicarbonate was the dominant anion in the monitoring points, whereas Na and K were the main cations, with Mg predominating in some cases. The barium content was generally higher in waters sampled during the rainy period. The hydrochemical data were subjected to statistical analysis that indicated that barium is inversely related to sulfate in the rainy period.
Keywords: Araxá city; Barreiro area; Carbonatite; Hydrochemistry; Niobium deposit; Phosphate mining